2020
DOI: 10.3390/ijerph17103409
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Effects of a Campus Forest Therapy Program

Abstract: This study aimed to examine the psychological effects of a campus forest therapy program. To evaluate these, pre-test and post-test control group design was employed. A total of 38 participants participated in this study (19 in the campus forest therapy program group, and 19 in control). The Profile of Mood State (POMS) questionnaire and Modified form of the Stress Response Inventory (SRI-MF) were administered to each participant to assess psychological effects. The results of this study revealed that particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…After the non-face-to-face programs were applied, the perceived stress level decreased immediately in both the experimental group and the control group, but the experimental group that watched the forest video showed a greater decrease over the three sessions. This aligns with the results of previous studies that found positive effects on stress when forest therapy was offered repeatedly rather than a single time (Kim et al, 2020;Song et al, 2014). In addition, although the non-face-to-face video program in this study was as short as 5 min, the finding that stress was reduced in both the experimental and control groups aligns with those of previous studies, which found that viewing a forest video of just a few minutes had positive effects on mental health regarding negative emotions, fatigue, and distress (Bielinis et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…After the non-face-to-face programs were applied, the perceived stress level decreased immediately in both the experimental group and the control group, but the experimental group that watched the forest video showed a greater decrease over the three sessions. This aligns with the results of previous studies that found positive effects on stress when forest therapy was offered repeatedly rather than a single time (Kim et al, 2020;Song et al, 2014). In addition, although the non-face-to-face video program in this study was as short as 5 min, the finding that stress was reduced in both the experimental and control groups aligns with those of previous studies, which found that viewing a forest video of just a few minutes had positive effects on mental health regarding negative emotions, fatigue, and distress (Bielinis et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…The psychological impact of forest therapy has received particular attention, since urban dwellers have an elevated risk of mental health difficulties associated with prolonged stress exposure (Lederbogen et al, 2011; Song et al, 2013). One forest therapy program that included folk dancing and other forest‐based exercises (such as stretching and walking) significantly improved mood and relieved stress (Kim et al, 2020). In another study, forest therapy that incorporated exercise and meditation led to a significant decrease in depression among people with alcoholism (Shin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The inner experience and the apparent behavior are a movement of unity and harmony. Kim, Khil, Lim, Park, Shin, and Shin (2020) also added some of the programs that can be done in forest therapy, including: Ice-breaking introduction: familiarity with forest and lecture on stress management; Clapping exercise: forest folk dance, stress reduction; Forest orienteering (using natural objects to solve group mission): physical stimulation…”
Section: Integral Healthmentioning
confidence: 99%
“…The physiological benefits include effects on the immune system (e.g., natural killer cells), insulin, oxidative stress, nervous system (e.g., heart rate), salivary cortisol, oxyhemoglobin, the cardio-circulatory system, and the respiratory system. In terms of social wellbeing, effects include social skills, emotional skills, self-esteem, and inspiration [ 4 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%